An Aspect of Strategies and Policies for Education in India - Amit Channa; Ardima Bajpai (AG Volumes, 2022)
As a developing nation, India relies on a strong educational system to ensure its continued economic and social progress. Courses at this level might range from the undergraduate to the postgraduate, and even to the PhD level. Furthermore, it is crucial in the development of future educators. As a result of the fact that it is necessary for continued existence, the purpose of this article is to examine recent developments in the educational system of India, as well as the issues that it now faces and potential solutions to those challenges. The argument is that these individual needs practical educations for certain of its jobs, therefore education is more than just the transfer of knowledge from trainer to student. After 34 years without a comprehensive education strategy, India now has one thanks to the publication of the National Education Policy (NEP) 2020.